Spatial distribution of trees on light taiga plots before selective thinning - Gradel, Alexander; Nadaldorj, Ochirragchaa; Altaev, Aleksandr A; Voinkov, Aleksandr A; Bazarradnaa, Enkhtuya (Mongolian Journal of Agricultural Sciences, 2015)
Since 2009 the School of Agroecology and Business, Institute of Plant and Agricultural Sciences of the Mongolian University of Life Sciences in Darkhan has established research plots in two research areas in the Selenge aimag. The establishment was conducted in close cooperation with development organisations (FAO, GIZ) and the University of Goettingen. The purpose of the research initiative is to combine capacity development and monitoring of forest structure in the mountain forest steppe zone and taiga zone. Here we report results on the horizontal spatial structure of forest stands. We analysed the spatial distribution of trees on birch and larch plots of the research area «Altansumber» before a selective thinning took place on some plots in 2009. The research area is situated in the mountain forest steppe zone. The forests belong to the light taiga. The selected stands approach a chronosequence. The results showed that the tree distributions were mainly irregular («clumped»).Random spatial tree distribution occurred especially in the medium-aged birch stand. We found no indication of regular tree distributions in any of the plots. We assume that the disturbance regime and successional processes are the driving factors leading to the specific tree distribution pattern on the plots. Due to different regeneration strategies and life span of the dominating species the birch stands and the larch stands seem to differ slightly concerning the chronological occurrence of clumped and random spatial tree distribution. We finally conclude that a better control of the disturbance regime would not only support an undisturbed forest succession to riper forest stands but also result in less forest stands with irregular spatial distribution. This may also have implications on forest productivity. Mongolian Journal of Agricultural Sciences Vol.15(2) 2015; 91-99